Turbinate-Specific IgE in Normal and Rhinitic Patients. Issue 2 (March 2019) - Hamizan, Aneeza W.; Rimmer, Janet; Alvarado, Raquel; Sewell, William A.; Tatersall, Jessica; Barham, Henry P.; Kalish, Larry; Harvey, Richard J.
Background: Specific immunoglobulin E (sIgE) within the nasal airway is likely to be the most ideal marker of allergic status, but little is known of the normative values in asymptomatic patients and those with rhinitis. Objective: The aim of this study was to assess the diagnostic characteristics of inferior turbinate tissue biopsy sIgE in asymptomatic and rhinitic patients. Methods: A diagnostic cross-sectional study was undertaken, involving patients who underwent inferior turbinate surgery with or without other surgical interventions. Inferior turbinate tissue biopsy was performed during surgery and was assessed for allergen sIgE (dust mite, grass [temperate or subtropical], and animal epithelium) using an automated immunoassay. Tissue sIgE was assessed among asymptomatic patients and those with nasal symptoms. Data were presented as median (interquartile range). A receiver operating curve was used to predict the diagnostic utility of turbinate tissue sIgE in determining allergic rhinitis. Results: A total of 160 patients (41.89 ± 14.65 years, 36.9% females) were included. The median tissue sIgE concentration among the asymptomatic nonatopic group of patients was 0.09 (0.08–0.10) kUA/L and tissue sIgE > 0.10 kUA/L was determined as a positive threshold. Inferior turbinate tissue sIgE was shown to be a predictive test for allergic rhinitis (area under curve: 0.87, 95% confidence interval: 0.84–0.90) with 90% sensitivity and 89% negative predictive value. Conclusion: Inferior turbinate tissue biopsy sIgE is a sensitive tool to predict allergic rhinitis. The threshold value of 0.1 kUA/L corresponded well with the asymptomatic nonatopic group of patients. This method detects sIgE in the nasal mucosa and may be a useful test for allergic rhinitis in future research.